Multifractal Analysis of Cardiac Series and Predictors of Sudden Cardiac Death - Kovalchuk, V.I.; Svechnikova, O.S.; Bulavin, L.A. (Ukrainian Journal of Physics, 2021)
In the framework of the multifractal formalism and using the wavelet-transform modulusmaxima method, the daily Holter monitoring records from the PhysioNet databases for sudden cardiac death and normal sinus rhythm have been analyzed. On the basis of successive window samples of the heart rate variability signals for the VFL range (0.0025–0.04 Hz), the time dependences of the widths of singularity spectra and the positions of their maxima are calculated. The average energy of low-frequency oscillations of the singularity spectrum width for the studied records of sudden cardiac death is found to be by 36% higher than the corresponding value for the records of normal sinus rhythm. This discrepancy can be considered as a predictor of sudden cardiac death.